Scientific selling creating high-performance sales teams through applied psychology and testing - Martini, Nancy, 1959- (Wiley, 2012)
"A truly scientific approach to measuring and improving sales performanceScientific Selling shows how statistically-valid measurement can improve every element of the sales environment&emdash;from management to coaching to training to creating long-term sustainable sales results. Sales organizations that embrace applied psychology and testing become more competitive because they don't waste resources on irrelevant or counterproductive activities. Managers can better assess the reasons behind individual and group performance and predictably improve sales results, while fostering a sales culture that attracts and retains personnel who have the personality and motivation to be successful.Scientific Selling includes more than a dozen specific stories demonstrating how scientific measurement improved overall sales performance through easily understood graphics, charts, and descriptions. It details how those teams were measured and how those metrics changed as the result of better hiring practices and better targeted coaching and sales training. Through these detailed case studies, Scientific Selling illustrates the importance of measurement for steering the success of your company. The book: Describes how the Clark-Mortenson Agency used scientifically proven data-based assessment tools to provide individual sales professionals with a very specific overview to determine their current strengths and areas of growth Examines Meadowbrook Golf's program to "manage for individual success" by using scientific testing and measurement to help its top managers understand what motivated their employees Details how Yankee Candle used scientific measurement to identify the right people to hire, and then used customer case studies and role-playing to focus on leveraging each individual's natural behavior to sell, thereby creating increases of 40% in sales revenue for trained individuals Scientific testing and measurement can leverage current strengths, identify areas for growth, and increase revenue. Chart your company's course through the power of Scientific Selling"--